The adequacy of telemedicine act relating to liability of telemedicine practitioners in Malaysia: a comparative study with telemedicine law of California, Usa / Nurul Fatihah Norull Bahri Saiful Abadi…[et al.]. - Norull Saiful Abadi, Nurul Fatihah; Mohd Zaki, Nurul Hafizah; Azman, Nurul Syahirah; Wan Ismail, Wan Fatin Najah (2012)
Telemedicine is newly practiced in Malaysia. This research focuses on the adequacy of Telemedicine law in Malaysia in governing liability of telemedicine practitioners. For this purpose, the relevant provisions in the Malaysian Telemedicine Act 1997 are reviewed. There are loopholes in the existing law that can be improved in order for the Government to achieve efficacy in practicing telemedicine. The new hack of proper procedures and approaches greatly affect the legal implications on the liability of telemedicine practitioners. To improve the law in Malaysia, a comparative analysis of the study is made with the Telemedicine Law in the California, USA. The research proposed the amendment of the Malaysian Telemedicine Act 1997.